The scope and limitations of a process of militarization of the indios amigos of Buenos Aires (1862-1876) - Gambetti, Nadia G. (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2013)
The paper studies the incorporation of the indios amigos (i.e. Indian friends) of Buenos Aires to the National Army between 1862 and 1876. We understand that this practice was an attempt to carry out a process of militarization, in order to control and discipline these indigenous groups. From this point, the paper analyzes the limits that the Indians placed on these attempts of subordination by the state and the role played by the border commanders. To address this issue we turn to a documentary corpus composed of correspondence between military authorities, border commanders and chieftains, and by official sources.